Digital identity for development: The quest for justice and a research agenda. Issue 1 (2nd January 2021) - Masiero, Silvia; Bailur, Savita
ABSTRACT: We pursue three main objectives in this editorial for the Special Issue on Identification in a Digital Age: Implications for Development. After outlining the motivations that led us to launch this Special Issue call, we first propose a framework to map the theoretical link between digital identity and human development, articulated in three dimensions linking digital identity to expected development outcomes. Secondly, we present the seven papers in this collection in terms of how they problematise such a link, observing how each of them uses empirical data to increase existing knowledge on this connection and question it. Thirdly, we leverage insights from these contributions to put forward a research agenda on digital identity and human development, suggesting possible avenues to engage with this topic and ultimately, framing digital identity as an object of ICT4D research.